Effects of Dietary Choline on Endogenous Phospholipid Synthesis in Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Yang Xu; Mengyu Shi; Ping Wu; Yuanqin Zhang; Samwel Mchele Limbu; Jinyun Ye; Changle Qi (Fishes, 2026)
This study investigated the effects of choline on endogenous phospholipid synthesis in Chinese mitten crab (Eriocheir sinensis). Chinese mitten crabs (0.40 ± 0.03 g) were fed diets supplemented with 0%, 0.2% or 0.4% choline under low phospholipids (low-PL) or normal phospholipids (normal-PL) for eight weeks. The results showed that feeding the Chinese mitten crab with 0.4% choline in low-PL diets up-regulated significantly the relative mRNA expressions of neuropathy target enzyme 1 (nte1), phospholipase A2 (pla2) and phospholipase B (plb). Moreover, the crabs fed the 0.4% diet at low-PL diets enhanced hepatopancreatic fatty acid binding protein 3 (fabp3), fatty acid transporter protein 4 (fatp4), carnitine palmitoyltransferase-2 (cpt-2), carnitine acetyltransferase (caat), carnitine palmitoyltransferase-1a (cpt-1a) and carnitine palmitoyltransferase-1b (cpt-1b). However, feeding the mitten crabs 0.2% choline in the normal-PL diets diets up-regulated significantly the relative mRNA expressions of nte1, pla2 and plb. These results indicate that 0.4% choline up-regulates the expressions of genes involving in phospholipids synthesis of Chinese mitten crab fed with low-PL diets, while 0.2% choline improved the genes involved in phospholipid decomposition under normal-PL conditions.

Effects of Dietary Protein Sources on Vitellogenin of Female Largemouth Bass (Micropterus salmoides) - Yue Tan; Yang Xu; Li Jia; Youqin Kong; Zhili Ding; Changle Qi; Qiyou Xu (Fishes, 2026)
To investigate the effects of three alternative protein sources—Hermetia illucens larvae meal (HIM), Chlorella meal (CM) and stickwater meal (SWM)—on the vitellogenin in female largemouth bass (Micropterus salmoides), these protein sources were used to replace 0% (control group, FM; containing 40% fishmeal), 25% and 50% of the fishmeal in the diet. A total of seven isonitrogenous and isolipidic diets were formulated (FM, 25% HIM, 50% HIM, 25% CM, 50% CM, 25% SWM and 50% SWM). The healthy female fish with an initial body weight of 353.57 ± 28.12 g were fed the experimental diets for eight weeks. The results showed that the viscerosomatic index, gonadosomatic index and oocyte diameter of broodstock in the 50% HIM group were significantly higher than those in the FM group. The 50% HIM group showed the highest rate of stage IV oocytes and the lowest share of stage II oocytes. Hepatic vitellogenin (Vg) mRNA expression was significantly upregulated in the 50% HIM group, whereas ovarian mRNA expression of Vg and vitellogenin receptor (VgR) was significantly upregulated in the 25% SWM and 50% SWM groups. In conclusion, replacing 50% of dietary fishmeal with Hermetia illucens larvae meal can promote ovarian development in largemouth bass broodstock by increasing the gonadosomatic index and the expression of genes involved in vitellogenin synthesis.

Research Progress and Application Prospects of Dietary Supplements in Growth and Immune Regulation of Aquatic Animals - Jianhua Ming; Qiyou Xu; Changle Qi; Fei Song; Chuanpeng Zhou (Fishes, 2025)
The global aquaculture industry faces increasing challenges, including the need to improve feed efficiency, reduce reliance on fishmeal, and mitigate disease risks while ensuring sustainable production [...]

Five new chromane meroditerpenoids from the brown alga Sargassum siliquastrum of China Sea - Junzhi Pan; Huayuan Liu; Junpeng Xu; Xiaofeng Xu; Yu Qi; Chaojie Wang; Changle Wu; Zhongmin Sun; Yali Lv; Pengcheng Yan (Phytochemistry Letters, 2024)

Effects of Soybean Isoflavones on the Growth Performance and Lipid Metabolism of the Juvenile Chinese Mitten Crab Eriocheir sinensis - Mengyu Shi; Yisong He; Jiajun Zheng; Yang Xu; Yue Tan; Li Jia; Liqiao Chen; Jinyun Ye; Changle Qi (Fishes, 2024)
In order to study the effects of soybean isoflavones on the growth performance and lipid metabolism of juvenile Chinese mitten crabs, six experimental diets were formulated by gradient supplementation with 0%, 0.004% and 0.008% soybean isoflavones at different dietary lipid levels (10% and 15%). The groups were named as follows: NF-0 group (10% fat and 0% SIFs), NF-0.004 group (10% fat and 0.004% SIFs), NF-0.008 group (10% fat and 0.008% SIFs), HF-0 group (15% fat and 0% SIFs), HF-0.004 group (15% fat and 0.004% SIFs) and HF-0.008 group (15% fat and 0.008% SIFs). All crabs with an initial weight of 0.4 ± 0.03 g were fed for 8 weeks. The results showed that dietary supplementation with 0.004% or 0.008% SIFs significantly increased the weight gain and specific growth rate of crabs. Diets supplemented with 0.004% or 0.008% SIFs significantly reduced the content of non-esterified free fatty acids and triglycerides in the hepatopancreas of crabs at the 10% dietary lipid level. Dietary SIFs significantly decreased the relative mRNA expressions of elongase of very-long-chain fatty acids 6 (elovl6), triglyceride lipase (tgl), sterol regulatory element-binding protein 1 (srebp-1), carnitine palmitoyltransferase-1a (cpt-1a), fatty acid transporter protein 4 (fatp4), carnitine palmitoyltransferase-2 (cpt-2), Δ9 fatty acyl desaturase (Δ9 fad), carnitine palmitoyltransferase-1b (cpt-1b), fatty acid-binding protein 10 (fabp10) and microsomal triglyceride transfer protein (mttp) in the hepatopancreas of crabs. At the 15% dietary lipid level, 0.008% SIFs significantly increased the relative mRNA expressions of fatty acid-binding protein 3 (fabp3), carnitine acetyltransferase (caat), fatp4, fabp10, tgl, cpt-1a, cpt-1b and cpt-2 and significantly down-regulated the relative mRNA expressions of Δ9 fad and srebp-1. In conclusion, SIFs can improve the growth and utilization of a high-fat diet by inhibiting genes related to lipid synthesis and promoting lipid decomposition in juvenile Chinese mitten crabs.

Effects of Dietary Glutamate on the Growth Performance and Antioxidant Capacity of Juvenile Chinese Mitten Crab (Eriocheir sinensis) - Jiajun Zheng; Yisong He; Mengyu Shi; Li Jia; Yang Xu; Yue Tan; Changle Qi; Jinyun Ye (Fishes, 2024)
In order to explore the effects of glutamate on the growth performance, antioxidant capacity and protein metabolism of juvenile Chinese mitten crab, 0%, 1% and 2% glutamate were supplemented to low protein (30%) and normal protein (35%) diets, respectively. There were 5 parallel tanks in each treatment, and the feeding duration was 8 weeks. The results showed that dietary glutamate did not significantly affect the weight gain of Chinese mitten crab. Diets supplemented with 2% glutamate significantly decreased the crude protein of crabs. The T-AOC of crabs fed the 30% protein diets was significantly lower than crabs fed the 35% protein diets. At 30% protein level, the superoxide dismutase (SOD) activity significantly increased with the increase in glutamate content. Dietary glutamate significantly down-regulated the relative expressions of mTOR, PI3K, S6K1 and 4EBP at 35% protein level. In conclusion, dietary glutamate cannot significantly increase the growth of Chinese mitten crab, but it can improve the antioxidant capacity in Chinese mitten crab under low protein conditions.

Effect of Dietary Supplementation on the Growth and Immunity of Fish and Shellfish - Changle Qi; Qiyou Xu; Jianhua Ming; Fei Song; Chuanpeng Zhou (Fishes, 2024)
With the rapid development of aquaculture, the shortage of high-quality dietary ingredients has become a critical problem limiting the sustainable development of aquaculture [...]

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Replacing fishmeal with soybean meal affects survival, antioxidant capacity, intestinal microbiota, and mRNA expression of TOR and S6K1 in Macrobrachium rosenbergii - Zhili Ding; Dongsheng Zhou; Jinxian Zheng; Xuefeng Chen; Youqin Kong; Changle Qi; Yan Liu; Qiongying Tang; Guoliang Yang; Jinyun Ye (Journal of Oceanology and Limnology, 2022)